The Philosophy of Science Management in the Era of Digitalization : An Initial Systematic Literature Review - Muchamad Rizky Fauzi; Hamdani Hamdani (International Journal of Economics, Commerce, and Management, 2025)
The digitalization of science management has profoundly reshaped how scientific research and development management are organized, directed, and executed. This present paper examines this transformation by conducting an initial systematic literature review. This paper identifies gaps, synthesizes findings, and draws conclusions by analyzing peer-reviewed articles from various sources. By synthesizing the key findings of recent studies, this review underlines five key themes, namely the growing emphasis on data-driven decision-making, the evolving role of leadership, the need for ethical and regulatory considerations, the opportunities for enhanced collaboration and cross-pollination of ideas, and the potential for improved decision-making and organizational agility. These findings underscore the need for science managers to adapt their strategies to harness the opportunities and address the challenges resulting from digitalization.